Princess Academy - Hale, Shannon (Bloomsbury Children's Books Distributed to the trade by Holtzbrinck Publishers, 2005)
While attending a strict academy for potential princesses with the other girls from her mountain village, fourteen-year-old Miri discovers unexpected talents and connections to her homeland.